Evaluasi Dampak Kinerja Proses Pembelajaran Terhadap Kepuasaan Mahasiswa : Studi Kasus pada Universitas XYZ di Kota Bandung - Nataliningsih; Gijanto Purbo Suseno (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
During the Covid-19 pandemic, the learning process in most universities is carried out online. The online learning process depends on the facilities used by lecturers who are assisted by Academic Staff as hosts and online participants, namely students. Some of the problems that often occur are poor signal, unclear sound or other unexpected disturbances. Therefore, it is necessary to evaluate the online learning process that has been carried out so far. This research was conducted at XYZ College which organizes 9 study programs, with a qualitative descriptive approach. The respondents were all online participating students, namely assessing the level of satisfaction in participating in online learning. The questionnaire uses a Likert scale of 1-4 which is very good, good, not good and not good. Each study program takes 2 courses without practicum and one carrying out practicum, then the average is taken for analysis. The results of the research show that the implementation of online lectures during the Covid 19 pandemic was carried out very satisfactorily, lecturers have worked hard to keep up with technological developments in learning methods and techniques and students have tried hard to be able to understand, take advantage of discussion opportunities and do assignments and exams very well. As a suggestion, it is necessary to further investigate the satisfaction of lecturers and education staff in carrying out their duties during the Covid 19 pandemic as input for institutions to develop the competence of lecturers and staff as well as the completeness of infrastructure facilities.